Photodynamics and quantum efficiency of germanium vacancy color centers in diamond - Nguyen, Minh; Nikolay, Niko; Bradac, Carlo; Kianinia, Mehran; Ekimov, Evgeny A.; Mendelson, Noah; Benson, Oliver; Aharonovich, Igor (Advanced Photonics, 2019)
Color centers in diamond-especially group IV defects-have been advanced as a viable solid-state platform for quantum photonics and information technologies. We investigate the photodynamics and characteristics of germanium-vacancy (GeV) centers hosted in high-pressure high-temperature diamond nanocrystals. Through back-focal plane imaging, we analyze the far-field radiation pattern of the investigated emitters and derive a crossed-dipole emission, which is strongly aligned along one axis. We use this information in combination with lifetime measurements to extract the decay rate statistics of the GeV emitters and determine their quantum efficiency, which we estimated to be ∼ (22 ± 2) %. Our results offer further insight into the photodynamic properties of the GeV center in nanodiamonds and confirm its suitability as a desirable system for quantum technologies.
CRIS-Team Scopus Importer:2023-04-20
Keywords: color center; germanium vacancy; nanodiamond; quantum efficiency